2022
DOI: 10.3390/vaccines10060857
|View full text |Cite
|
Sign up to set email alerts
|

Routine Immunization Programs for Children during the COVID-19 Pandemic in Ecuador, 2020—Hidden Effects, Predictable Consequences

Abstract: The COVID-19 pandemic has led to a global disruption of several services, including routine immunizations. This effect has been described in several countries, but there are few detailed studies in Latin America and no reports in Ecuador. Therefore, this work aims to quantify the reduction in routine immunizations for infants during the 2020 COVID-19 pandemic in Ecuador. 2018, 2019, and 2020 data were obtained from the Ministry of Health, Ecuador. The number of doses and the extent of immunization coverage was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The literature also supported the reports of decreased immunization coverage during the COVID-19 pandemic, where the pandemic affected routine immunization globally and a greater effect was expected in LMICs [ 23 , 34 , 35 , 36 , 37 ]. A recent study conducted in Ecuador (an LMIC) that aimed to assess the vaccination coverage during the pandemic in 2020 reported a decreased number of vaccine doses and vaccination coverage for infants for the rotavirus, poliovirus, PCV, and pentavalent vaccines as compared to previous years [ 20 ]. The study also explained that the causes of decreased vaccination coverage could be related to parental choices to use another method for immunity, misconception, national lockdowns, mobilization restrictions, and fear of infection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature also supported the reports of decreased immunization coverage during the COVID-19 pandemic, where the pandemic affected routine immunization globally and a greater effect was expected in LMICs [ 23 , 34 , 35 , 36 , 37 ]. A recent study conducted in Ecuador (an LMIC) that aimed to assess the vaccination coverage during the pandemic in 2020 reported a decreased number of vaccine doses and vaccination coverage for infants for the rotavirus, poliovirus, PCV, and pentavalent vaccines as compared to previous years [ 20 ]. The study also explained that the causes of decreased vaccination coverage could be related to parental choices to use another method for immunity, misconception, national lockdowns, mobilization restrictions, and fear of infection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the global coverage of the first dose of measles-containing vaccine (MCV1) decreased from 86% in 2019 to 84% in 2020 [ 7 ]. Several studies addressed the effect of the pandemic on child health globally, especially childhood vaccination, and confirmed the decline in routine vaccination coverage in children in numerous countries, especially in low- and middle-income countries (LMICs) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the future outbreaks, we cannot fall into some of the mistakes done during the COVID-19 pandemic [65]. We have to work on the impacts of COVID-19 on other infectious diseases, such as the decrease of vaccine coverages against other vaccine-preventable diseases [66], as well as to deal with long-COVID-19 syndrome [67], among others.…”
Section: Discussionmentioning
confidence: 99%
“…These limited economic and social aid policies have resulted in significant reductions in the coverage of health supplies and medications for chronic patients, maternal health, and sexual and reproductive health as well as unequal vaccine access [24]. In this context, a few studies conducted in Ecuador reported an increased prevalence of psychological distress symptoms [25].…”
Section: Introductionmentioning
confidence: 99%